2010
DOI: 10.3390/molecules15031578
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, Spectral and Thermal Studies of New Rutin Vanadyl Complexes

Abstract: Complexes between oxovanadium (IV) cation and flavonoid derivatives were developed recently in order to increase the intestinal absorption and to reduce the toxicity of vanadium compounds. For these reasons, is interesting to investigate the complexation process between flavonoid rutin (Rut) and vanadyl cation in order to isolate new complexes. Two new complexes [VO(Rut)(H2O)2](SO4)0.5 2H2O and [VO(Rut)2] 4H2O have been obtained and characterized by elemental and thermal analyses and several spectroscopic tech… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
30
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 63 publications
(31 citation statements)
references
References 35 publications
1
30
0
Order By: Relevance
“…15,16 They can interact with metal ions via three domains including the dihydroxy group (3 0 -OH and 4 0 -OH) in the B ring, the 3-OH or 5-OH and the 4-CO groups in the C ring ( Fig. 1).…”
Section: -11mentioning
confidence: 99%
See 2 more Smart Citations
“…15,16 They can interact with metal ions via three domains including the dihydroxy group (3 0 -OH and 4 0 -OH) in the B ring, the 3-OH or 5-OH and the 4-CO groups in the C ring ( Fig. 1).…”
Section: -11mentioning
confidence: 99%
“…Despite increasing studies of various metal-avonoids complex and their biological activities, 11,15,17,18,21,22 research about the complexation between luteolin and manganese(II) cation has been limited. Therefore, the purpose of the present study was to examine the complex formation between luteolin and manganese(II) cation and conrm the complexation sites in luteolin by means of UV-visible spectroscopy, infrared spectroscopy, thermogravimetric analysis and elemental analysis.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…From these energy maps, it is concluded that good antioxidant efficiency of flavone is ensured by the increased number of OH groups on the skeleton and attenuation of the formation of phenoxyl radicals derived from these groups. The most stable radicals originating in the course of antioxidative action may be attributed to OH groups at the position C3 on the ring C, hydroxyl groups at mutual ortho positions at C3', C4' or C4' and C5' on the ring B and the various positions on the ring A (Uivarosi et al, 2010). The antioxidant efficiency of flavone also depends on the stability of the formed phenoxyl radical.…”
Section: Resultsmentioning
confidence: 99%
“…In order to combat against Cd-induced oxidative renal damage, antioxidant phytochemicals may be the suitable antidotes because of their high antioxidant nature and low toxicity. The flavonoids are a family of phenolic compounds that possess a remarkable spectrum of biochemical and pharmacological activities like antibacterial, antiviral, antiinflammatory, antiallergic, antithrombotic, antimutagenic, antineoplastic, as well as neuroprotective properties [14]. Mentha piperita (Lamiaceae), the peppermint (mint) plant is an aromatic perennial herb cultivated in most part of the world, have traditionally been used in folk medicine.…”
Section: Introductionmentioning
confidence: 99%